Analisis Penerapan Good Corporate Governance Dalam Meningkatkan Kinerja Perusahaan Pada Sub Holding Pt. Pelindo Multi Terminal - Muhammad Iqbal; Cindy Anggreni; Jihan Suwifania; Regi Anika (STIKes Ibnu Sina Ajibarang, 2024)
This mini-research aims to analyze the principles of implementing GCG which include transparency, accountability, responsibility, independence and justice, which are fundamental in managing business, especially in state-owned companies as regulated in the Regulation of the Minister of State for State-Owned Enterprises Number: PER – 01/MBU/2011 regarding the Implementation of Good Corporate Governance. The implementation of good corporate governance in the company has not been optimal due to a lack of socialization to communicate, educate and convey information about GCG to employees based on position holders. This research uses qualitative research methods with informants from related positions, company employees and service users. The results of the research show a lack of socialization from office holders so that new employees do not understand GCG, the principles of accountability, starting from the delivery of information and financial reports, have not been implemented quickly, and the principles of responsibility in service sessions have not been maximized, as shown by, among other things, limited internet access and provide comfort and satisfaction to customers.